2020
DOI: 10.1039/d0ew00316f
|View full text |Cite
|
Sign up to set email alerts
|

UV/chlorine vs. UV/H2O2 for water reuse at Orange County Water District, CA: a pilot study

Abstract: On-site demonstration tests evaluated 1,4-dioxane removal in reverse osmosis permeate (RO permeate) at the Orange County Water District (OCWD) Advanced Water Purification Facility (AWPF). The study used a pilot-scale ultraviolet...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 51 publications
0
40
0
Order By: Relevance
“…In industrial full-scale AOP applications, a H 2 O 2 concentration of 1–4 mg L –1 (0.03–0.12 mM) is typically used. A contour plot describing the H 2 O 2 concentration in a cell outlet at different cell currents and cell electrolyte flow rates was constructed to demonstrate the feasibility of generating highly concentrated H 2 O 2 , orders of magnitude higher than the concentration typically required for an AOP (Figure e). Note that the higher cell current could be readily achieved by cell scale-up, such as enlarging the electrode area, stacking layers of electrodes, and operating more reactors. , With considerations of real-world applications, air was supplied to cathode instead of ultrapure O 2 gas.…”
Section: Resultsmentioning
confidence: 99%
“…In industrial full-scale AOP applications, a H 2 O 2 concentration of 1–4 mg L –1 (0.03–0.12 mM) is typically used. A contour plot describing the H 2 O 2 concentration in a cell outlet at different cell currents and cell electrolyte flow rates was constructed to demonstrate the feasibility of generating highly concentrated H 2 O 2 , orders of magnitude higher than the concentration typically required for an AOP (Figure e). Note that the higher cell current could be readily achieved by cell scale-up, such as enlarging the electrode area, stacking layers of electrodes, and operating more reactors. , With considerations of real-world applications, air was supplied to cathode instead of ultrapure O 2 gas.…”
Section: Resultsmentioning
confidence: 99%
“…Although photolysis of H 2 O 2 is characterized by a relatively high quantum yield ( ∼1 for HO  production, and ∼0.5 for H 2 O 2 loss), its contribution to the degradation of target pollutants in real water matrices may be reduced due to the absorption of light by dissolved organic matter. 12,22 Moreover, H 2 O 2 overdosing results in HO  scavenging with formation of HO 2  (6): 23 H 2 O 2 + HO  → HO 2  + Н 2 Ο (6) Despite these limitations, possibly it is the only one HP-AOP applied at full scale so far in potable water reuse 24,25 and it is used as benchmark in different research works for comparison with other AOPs or treatment methods.…”
Section: Uv/h 2 Omentioning
confidence: 99%
“…OCl -+ HO  → + ClO  + OH - (11) HOCl + Cl  → ClO  + H + + Cl - (12) OCl -+ Cl  → ClO  + Cl - (13) This process is arousing growing interest as a possible alternative to the UV/H 2 O 2 process 25 or as a solution to limit the formation of chlorination by-products 31 .…”
Section: Uv/h 2 Omentioning
confidence: 99%
“…22 A similar study completed at the OCWD also found that UV/NH 2 Cl had the lowest performance for 1,4-dioxane removal upon comparison of UV/NH 2 Cl, UV/ HOCl, and UV/H 2 O 2 and that the decay did not follow pseudofirst-order kinetics. 26 This study found results similar to those of the pilot study completed by Zhang et al, who found UV/HOCl performed the best of the three AOPs for 1,4-dioxane removal, but also that nitrite ions present in the RO permeate significantly impacted process performance. 22 22 However, the total halogenated DBP concentrations were low (<15 μg/L) for all three AOPs.…”
Section: Introductionmentioning
confidence: 99%
“…The Orange County Water District (OCWD) in Fountain Valley, CA, was the first to employ UV/H 2 O 2 on a large scale for potable reuse after the 1999 discovery of NDMA and 1,4-dioxane in the OCWD seawater intrusion barrier, where reclaimed water is injected into the ground . Recent interest in alternatives to the UV-AOP oxidant H 2 O 2 , such as chlorine and monochloramine, has resulted in a number of published studies on UV/free chlorine (i.e., UV/HOCl) and UV/chloramines (i.e., UV/NH 2 Cl, though both mono- and dichloramine may be present). UV/HOCl (dosed as NaOCl) has been implemented in some newly commissioned reuse facilities. When chloramines are applied during upstream FAT treatment to prevent microfiltration/ultrafiltration (MF/UF) and RO membrane biofouling, residual chloramines persist through RO, such that UV/HOCl is actually a mixed UV/HOCl/chloramines AOP and, similarly, UV/H 2 O 2 is a mixed UV/H 2 O 2 /chloramines AOP. , The UV/chloramines AOP could theoretically employ the residual chloramine concentration present in the RO permeate or could be supplemented with additional chloramines if necessary.…”
Section: Introductionmentioning
confidence: 99%